Youth health behaviors and their reverse intergenerational impact - Xia, Shaoang; Zhang, Ke; Yan, Chuwen; Zhou, Yayu; Xiao, Chunqu (Frontiers in Psychology, 2025)
IntroductionIn the context of rapid population aging and digital transformation in China, youths are increasingly influencing older family members' health perceptions and behaviors through “cultural feedback” mechanisms. This study examines the factors shaping youth health behaviors and their reverse intergenerational effects on elders.MethodsA cross-sectional survey of 2,187 participants aged 18–35 examined factors influencing youth health behaviors and their reverse intergenerational influence on older family members, using regression analyses with mediation models.ResultsFindings indicate emotional regulation capacity emerged as the strongest predictor of health behaviors, followed by surrounding individuals‘ health status, gender, and self-reported health condition. Socioeconomic status, occupation, and age demonstrated limited direct effects. Young adults' health behaviors significantly predicted reverse intergenerational influence, with health behavior tendency mediating relationships between individual characteristics and intergenerational influence.DiscussionYoung adults serve as pivotal agents in health-related “cultural feedback”. Their health behavior tendencies subsequently influence older generations' health perceptions and practices. Interventions targeting emotional regulation skills among young adults may effectively amplify intergenerational health promotion while addressing aging-related public health challenges.